Improvement of Communicative English Language Teaching Quality of School English Teachers in Tha Muang and Koh Kaew Subdistrict, Selaphum District, Roi Et Province - Jantasin, Poonsuk; Pantawee , Thanaporn (Journal of Roi Et Rajabhat University, 2020)
The objectives of this research were to 1) study the instructional conditions, problems and the needs to improve English language teaching for communication recommended by English teachers in schools in Tha Muang, Koh Kaew Subdistrict, Selaphum District, Roi Et province; 2) examine the participants' opinions towards the communicative English teaching training course developed by the researcher. The samples included 11 English teachers under 9 schools in Tha Muang, Koh Kaew Subdistrict, Selaphum District, Roi Et province. The research instruments used in this study were a semi-structured interview and questionnaire on opinions towards English training course. Qualitative data were analyzed by using content analysis and quantitative data was analyzed by using percentage, mean and standard deviation. The results of the study included 7 aspects affecting efficiency in English instruction as follows: 1) the teachers’ inefficient application of content based on the core curriculum for communicative language teaching, 2) the lack of English teaching competency of non-English major teachers, 3) heavy teaching workload, 4) the lack of skills in using teaching materials for communicative language teaching, 5) discontinuity of the content of English course books in each level which are approved by the Ministry of Education, 6) limitations of internet signal causing difficulties in authentic use via online social medias and 7) insufficient budget provided directly for the improvement of student English proficiency and for material development in language learning management. The evaluation results of the participants' opinions towards the communicative English teaching training course developed by the researcher were at the highest level in overall.